2012
DOI: 10.1111/j.1582-4934.2012.01612.x
|View full text |Cite
|
Sign up to set email alerts
|

Eph receptors and ephrins as targets for cancer therapy

Abstract: Eph receptor tyrosine kinases and their ephrin ligands are involved in various signalling pathways and mediate critical steps of a wide variety of physiological and pathological processes. Increasing experimental evidence demonstrates that both Eph receptor and ephrin ligands are overexpressed in a number of human tumours, and are associated with tumour growth, invasiveness and metastasis. In this regard, the Eph/ephrin system provides the foundation for potentially exciting new targets for anticancer therapie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
110
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 204 publications
(261 reference statements)
1
110
2
Order By: Relevance
“…Eph receptors, with 16 known members, belong to the receptor tyrosine kinases (RTK)s family playing critical roles in many physiological processes, including embryonic tissue patterning, neuronal development, angiogenesis, and tumorigenesis (1)(2)(3)(4). Ephrins and Eph receptors are divided into two subclasses, A and B, and with some exceptions, eAs bind EphA-type receptors and ephrin-Bs (eBs) bind EphBs.…”
Section: Ephrin-a1 (Ea1)mentioning
confidence: 99%
“…Eph receptors, with 16 known members, belong to the receptor tyrosine kinases (RTK)s family playing critical roles in many physiological processes, including embryonic tissue patterning, neuronal development, angiogenesis, and tumorigenesis (1)(2)(3)(4). Ephrins and Eph receptors are divided into two subclasses, A and B, and with some exceptions, eAs bind EphA-type receptors and ephrin-Bs (eBs) bind EphBs.…”
Section: Ephrin-a1 (Ea1)mentioning
confidence: 99%
“…One such link can be provided by the Eph/ephrin family of the receptor tyrosine kinases known to play critical roles in lymphocyte differentiation (Cejalvo et al, 2013;Himanen et al, 2007). Upregulation of the Ephrin signaling pathway is one commonly found marker strongly associated with the oncogenic transformation (Pasquale, 2010;Xi et al, 2012). Most cases of NLH are lymphomas originated from B cell at various stages of differentiation and dysregulation of normal Ephrin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the correlation between HIF-2α and VEGFA expression was found to be negative, possibly due to an insufficient quantity and/or quality of samples. The ephrin (Eph) receptors are the largest known family of tyrosine kinases and are divided into two subclasses: Eph-A and Eph-B (32). EphA2 belongs to the EphA subclass, and is expressed at a minimal level in epithelial cells (33).…”
Section: Discussionmentioning
confidence: 99%